ALMA reveals optically thin, highly excited CO gas in the jet-driven winds of the galaxy IC 5063 - Dasyra, K. M.; Combes, F.; Oosterloo, T.; Oonk, J. B. R.; Morganti, R.; Salomé, P.; Vlahakis, N. (2016)
Using CO (4-3) and (2-1) Atacama Large Millimeter Array (ALMA) data, we prove that the molecular gas in the jet-driven winds of the galaxy IC 5063 is more highly excited than the rest of the molecular gas in the disk of the same galaxy. On average, the CO(4 - 3) /CO(2 - 1) flux ratio is 1 for the disk and 5 for the jet accelerated or impacted gas. Spatially-resolved maps reveal that in regions associated with winds, the CO(4 - 3) /CO(2 - 1) flux ratio significantly exceeds the upper limit of 4 for optically thick gas. It frequently takes values between 5 and 11, and it occasionally further approaches the upper limit of 16 for optically thin gas. Excitation temperatures of 30-100 K are common for the molecules in these regions. If all of the outflowing molecular gas is optically thin, at 30-50 K, then its mass is 2 × 106 M⊙. This lower mass limit is an order of magnitude below the mass derived from the CO(2 - 1) flux in the case of optically thick gas. Molecular winds can thus be less massive, but more easily detectable at high z than they were previously thought to be.
Keywords: Astrophysics - Astrophysics of Galaxies; galaxies: active; galaxies: nuclei; ISM: jets and outflows; ISM: kinematics and dynamics; ISM: molecules; submillimeter: ISM